GE_GERICHTE P/11115/2011 vom 3. April 2014 - GE Cour de justice (2014)
VIOL ; CRUAUTÉ ; MISE EN DANGER DE LA VIE D'AUTRUI(ART. 129 CP) ; LÉSION CORPORELLE SIMPLE | CP.123.5.2 CP.129 CP.139.1 CP.190.3 LEtr.115.1 A LEtr.115.1 B LEtr.115.1 C